TINJAUAN FIKIH KONTEMPORER TERHADAPHUKUM ASURANSI KESEHATAN DI PESANTREN - Hamdan Yuhafi; Abdul Wahab Abd Muhaimin; M. Dawud Arif Khan (Program Studi Ekonomi Syariah, 2023)
The principle of sharia health insurance is Takaful, in the sense of muamalah is mutual risk-bearing among others so that one with the other becomes the insurer of the risk of the other. This research examines the practice of Islamic insurance in the environment of the Modern Pesantren Ummul Quro al-Islami Bogor. This thesis research uses a qualitative method in the form of a case study with a descriptive analysis approach that uses primary data through interviews with the Modern Pesantren Ummul Quro, experts, and documentation, while for secondary data researchers use documents, journals, regulations, books, and scientific works related to the theory of insurance and sharia reinsurance. The results of the study indicate that; First, Some contemporary fiqh scholars state that health insurance is acceptable in Islam if it is carried out with principles that are in accordance with sharia law with the opinion that health insurance is permissible in sharia if it emphasizes the importance of avoiding elements of riba' (interest) and elements of maisir (gambling) in insurance agreements. Second, the health insurance system at the Ummul Quro al-Islami Modern Islamic Boarding School in Bogor uses a tabarru'bil hibah contract, namely a grant contract from participants (santri) with the Islamic Boarding School as a grant manager named Poskestren. The basic objective in the implementation of shariah health insurance under Poskestren is to provide basic health services, including promotive (maintaining health), preventive (preventing), rehabilitative (restoring health) and curative (treatment) efforts. Third, health insurance at the Modern Islamic Boarding School Ummul Quro al-Islami Bogor has paid attention to aspects of insurance in the principles of Tahuhid (Unity), Justice (Justice), Mutual Aid (Ta'awun), Amanah (Trustworthy), Avoiding gambling (Maisir), and prioritizing the value of empathy. although in practice the management of sharia insurance at the Modern Islamic Boarding School Ummul Quro al-Islami has not been supervised by the Sharia Supervisory Board (DPS)